Continuing Professional Development Needs: Are Elementary School Teachers in Rural Areas Ready to Take the Online Training? - Yudi Yanuar; Wahyu Sopandi; Udin Syaefudin Sa'ud; Cepi Riyana (International Conference on Elementary Education, 2023)
Continuous professional development (CPD) has a significant impact on the competency of elementary school teachers. This study aimed to investigate the readiness of elementary school teachers in rural areas to attend online training based on their professional development needs—quantitative research methods with a descriptive approach. The research sample was 94 elementary school teachers in a rural area of one of the districts in West Bandung Regency, West Java, which were taken using a purposive sampling technique. Data was collected through a questionnaire using the Guttmann scale and focused group discussion (FGD). The questionnaire consists of 8 questions in 3 indicators to be studied. While the discussion was concentrated, five questions were asked of the respondents. The study results show that elementary school teachers in rural areas are ready to participate in continuous professional development through online training according to their level of need and mastery of the subject matter. It can be a reference for further research to develop online training that does not only involve teachers from urban areas and can also involve teachers from rural areas.